Development of antibiotics and the future of marine microorganisms to stem the tide of antibiotic resistance - Kasanah, Noer (Curr Opin Investig Drugs, 2004)
Antibiotics remain essential tools in the control of infectious diseases. With the emergence of new diseases, resistant forms of diseases such as tuberculosis and malaria, as well as the emergence of multidrug-resistant bacteria, it has become essential to develop novel antibiotics. Development of the existing antibiotics involved three strategies, including discovery of new target sites, modification of existing antibiotic structures, and the identification of new resources for novel antibiotics. Marine microorganisms have clearly become an essential new resource in the discovery of new antibiotic leads.